Increasing energy efficiency and reducing energy costs through the creation of national standards (Вестник КазНУ. Серия Экономическая, 2016)
In recent decades, the energy that began to make significant cost hasbecome a key aspect. As before the energy has always been a resource forproduction, it has become recognized as one of the main sources of coststhat deserves serious attention. Developing energy management conceptinvolves energy management as any other productive resources to reduceenterprise costs by improving energy efficiency. There are a number ofstandards in the field of Energy Efficiency, but they do not take into accountthe specific characteristics of the country, it is proposed the useof National Energy Efficiency Standard. Industry is a major consumer ofelectricity (70%) and thermal energy (50%), the population consumes lessthan 25% of electricity and 30% heat.